Papel dos receptores kappa opioides e sua interação com receptores 5-HT1A no teste da estimulação elétrica na substância cinzenta periaquedutal dorsal de ratos - Almeida, Camila Biesdorf de (2014)
Panic disorder (PD) is characterized by repeated occurrence of spontaneous panic attacks (PAs), followed by chronic anxiety. The susceptibility to PA in PD patients is due to a deficient serotonergic and opioidergic mechanism and the dorsal periaqueductal gray (DPAG) assumes a pivotal role in the regulation of PAs. Studies show that 5-HT1A receptors are involved in the regulation of defensive behavior in this cerebral area. Furthermore, the activation of kappa (κ) opioid receptors of the DPAG promote aversive effects. The aim of this study was verify the involvement of κ receptors and their interaction with 5-HT1A receptors placed in this cerebral area, in rats submitted to electrical stimulation test in the DPAG, an animal model that studies the pathophysiology and treatment of PD. Male Wistar rats were microinjected (0.2 μL/120s) into DPAG with the κ-opiod antagonist Nor-BNI (3.4 and 6.8 nmol) or 5-HT1A agonist, 8-OHDPAT (0.8 and 1.6 nmol), as well the association of Nor-BNI (3.4 nmol) with 8-OHDPAT (0.8 nmol) and submitted to electrical stimulation test, which was measured the intensity of electrical that evoked escape behavior (escape threshold) before and after the drugs treatment to investigate possible effects. The higher doses of Nor-BNI (6.8 nmol) and of 8-OHDPAT (1.6 nmol) promoted increase on the threshold escape, indicative panicolytic-like effect. The association of ineffective doses of the Nor-BNI (3.4 nmol) with 8-OHDPAT (0.8 nmol), also showed increase on the threshold escape statistically significant when compared to control group. Data were analyzed by one-way ANOVA followed by the post hoc Duncan's test. These results show that the κ receptors are involved in aversion and act cooperatively with 5-HT1A receptors on the regulation of escape responses promoted by DPAG electrical stimulation.